Validation of a multiplex RT-PCR assay for screening significant oncogene fusion transcripts in children with acute lymphoblastic leukaemia - Ariffin, H.; Chen, S.P.; Wong, H-L; Yeoh, A. (Stamford Publishing, 2003)
In childhood acute lymphoblastic leukaemia (ALL), cytogenetics play an important role in diagnosis, allocation of treatment and prognosis. Conventional cytogenetic analysis, involving mainly karyotyping in our experience, has not been successful in a large proportion of cases due to inadequate metaphase spreads and poor chromosome morphology. Our aim is to develop a highly sensitive and specific method to screen simultaneously for the four most frequent fusion transcripts resulting from specific chromosomal translocations, namely, both the CML- and ALLtype BCR-ABL transcripts of t(9;22), E2A-PBX1 transcript of t(1;19), the MLL-AF4 transcript of t(4;11) and TEL-AML1 (also termed ETV6-CBFA2) of the cryptic t(12;21). A multiplex reverse transcription polymerase chain reaction protocol (RT-PCR) was developed and tested out on archival bone marrow samples and leukaemia cell lines. In all samples with a known translocation detected by cytogenetic techniques, the same translocation was identified by the multiplex-PCR assay. Multiplex RT-PCR assay is an effective, sensitive, accurate and cost-effective diagnostic tool which can improve our ability to accurately and rapidly risk-stratify patients with childhood ALL.